Building the Halal Dining Experience: Physical Evidence, Satisfaction, and Revisit Intention in Banda Aceh - Syahriyal Syahriyal; Muhammad Haris Riyaldi; Raisa Ullya Nisva; Fahrul Radhi (universitas teuku umar, 2025)
This study investigates how physical evidence in Middle Eastern–themed restaurants influences revisit intention in Banda Aceh and whether Muslim customer satisfaction mediates that relationship. Motivated by the growth of halal dining and the centrality of servicescape to Muslim diners’ experiences, the research addresses limited empirical evidence in this specific cultural setting. A cross-sectional survey was administered to 300 Muslim customers who had visited at least one target restaurant; responses were captured on a five-point Likert scale using reflective indicators for physical evidence, customer satisfaction, and revisit intention. Data were analyzed with partial least squares structural equation modeling (SmartPLS 3.0) and bootstrapping. Measurement results showed strong reliability and convergent–discriminant validity across constructs. Structurally, physical evidence had a significant positive effect on customer satisfaction and revisit intention, while customer satisfaction also significantly increased revisit intention. The model explained a substantial share of variance in customer satisfaction and revisit intention, and mediation testing indicated that customer satisfaction partially carried the effect of physical evidence on revisit intention. These findings highlight that an Islamic-aligned servicescape—covering architecture and interior, Islamic visual cues, cleanliness, absence of non-sharia activities, prayer facilities, and transparent transactions—directly encourages return visits and, through enhanced satisfaction, further strengthens customers’ intentions to revisit. The study contributes context-specific evidence for halal hospitality management and suggests that operators should jointly invest in servicescape design and experience orchestration to build repeat patronage.